Species-specific accumulation of polybrominated diphenyl ethers (PBDEs) and other emerging flame retardants in several species of birds from Korea. (December 2016) - Jin, Xiangzi; Lee, Sunggyu; Jeong, Yunsun; Yu, Jae-Pyoung; Baek, Woon Kee; Shin, Kyung-Hoon; Kannan, Kurunthachalam; Moon, Hyo-Bang
Abstract: Few studies have been conducted on the alternatives to legacy flame retardants in avian species worldwide. In this study, polybrominated diphenyl ethers (PBDEs) and alternative flame retardants such as novel brominated flame retardants (NBFRs) and dechlorane plus (DP) were determined in livers of 10 species of birds from Korea to elucidate species-specific accumulation, biological factors that affect accumulation, and bioaccumulation potentials of these contaminants. Among the emerging alternative flame retardants, the highest occurrence was found for bis(2-ethylhexyl)-3, 4, 5, 6-tetrabromo-phthalate (BEHTBP), syn -DP, anti -DP, and decabromodiphenyl ethane (DBDPE). PBDE concentrations (median: 17.1 ng/g lipid wt) measured in our study were within the ranges reported in previous studies, while the concentrations of BEHTBP, BTBPE and DP were greater than those reported earlier. Residential predatory birds showed significantly greater concentrations of PBDEs and NBFRs than migratory predators and passerine birds. The concentrations of PBDEs, BEHTBP, and DP in residential predatory birds were significantly correlated with increasing stable nitrogen isotope ratio (δ 15 N), which indicated biomagnification potentials of these contaminants. Our results suggest that the concentrations and accumulation patterns of PBDEs, NBFRs, and DP depend on the feeding habits and migration patterns of avian species. This is the first report on the accumulation of emerging alternatives to PBDEs in birds from Korea. Graphical abstract: Highlights: PBDEs, NBFRs, and DP were detected in liver tissues of 10 Korean bird species. BEHTBP, DP, and DBDPE showed higher detection rates. The highest levels of DP were found in Korean bird on a global scale. Contamination levels and congener profiles of PBDEs varied by diet and habitat. PBDEs, BEHTBP, and DP biomagnified in residential predatory birds. Abstract : Species-specific accumulation of PBDEs, NBFRs, and DP was found for various species of birds and these contaminants biomagnified in residential predatory birds from Korea.